Estimation of the Survival Benefit Obtainable From Screening for the Early Detection of Pancreatic Cancer. Issue 5 (May 2016) - Cucchetti, Alessandro; Ercolani, Giorgio; Cescon, Matteo; Brandi, Giovanni; Taffurelli, Giovanni; Maroni, Lorenzo; Ravaioli, Matteo; Pezzilli, Raffaele; Pinna, Antonio Daniele
Abstract : Objective: The chance to improve survival from pancreatic adenocarcinoma relies on early diagnosis through screening, but any screening program is subject to lead-time bias and no data are available in this regard. Aim of the present study was to evaluate the benefit obtainable from a screening program for early detection of pancreatic adenocarcinoma, considering screen-related biases. Methods: Monte Carlo simulation was performed using data from 1000 pancreatic cancer patients admitted in a tertiary referral hospital and from pertinent literature. Lead-time bias was assessed and subtracted from expected survival. Results: Mean expected life expectancy was 13.0 months. Assuming a 20%, 30%, or 50% stage III/IV reduction with screening, pancreatic resections would increase from 217 to 290 in front of a 20% stage III/IV reduction to 324 in front of a 30% reduction and to 385 in front of a 50% reduction. After lead-time adjustment, life expectancies were 14.0, 14.6, and 15.9 months, respectively. The number-needed-to-screen calculation suggests that screening can be harmful in a proportion of patients inversely dependent on the length of follow-up and a significant improvement of survival after diagnosis. Conclusions: Pancreatic adenocarcinoma screening program would probably be successful in the presence of a considerable improvement of postdiagnostic survival; otherwise, it only increases surgical procedure amount.